2012
DOI: 10.1095/biolreprod.111.092445
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Use of Surrogate Mothers for Embryo Transfer in the Mouse

Abstract: Embryo transfer in mice is a crucial technique for generation of transgenic animals, rederivation of contaminated lines, and revitalization of cryopreserved strains, and it is a key component of assisted reproduction techniques. It is common practice to use females only once as surrogate mothers. However, their reuse for a second embryo transfer could provide hygienic and economic advantages and conform to the concept of the 3Rs (replace, reduce, refine). This investigation evaluated the potential for a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Therefore, the results presented here for the outcome after embryo transfer of freshly collected or cryothawed embryos might be inferior to results published earlier. 10,11 Nevertheless, we thought that retrospective analyses of more than 1300 embryo transfers could give an overall estimation for better planning and performance of embryo transfers, because heterogeneity of the background strains was equal for all groups and could therefore be disregarded here. The number of transferred freshly collected embryos influenced the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the results presented here for the outcome after embryo transfer of freshly collected or cryothawed embryos might be inferior to results published earlier. 10,11 Nevertheless, we thought that retrospective analyses of more than 1300 embryo transfers could give an overall estimation for better planning and performance of embryo transfers, because heterogeneity of the background strains was equal for all groups and could therefore be disregarded here. The number of transferred freshly collected embryos influenced the pregnancy rate.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that suboptimal conditions during the periconception period induce gene expression and epigenetic changes in gametes and embryos that can be maintained during post-implantation development [2]. In particular, alterations have been described at genetic and epigenetic level in placentas derived from in vitro fertilization, intracytoplasmic sperm injection or in vitro culture of embryos [22,23,24].…”
Section: Discussionmentioning
confidence: 99%
“…27 As we can exclude external stressors, we assume that this is a residual impact from the prior five-day training period.…”
Section: Discussionmentioning
confidence: 99%